(Re)Framing Our Frames: Architectonics, Intertextuality, and the Scholarship of Integration in Online Education - Dennis, Jeremy (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
The pandemic of 2020 has renewed interest in technology as an integrative agent in higher education. However, advancements in technology continue to outpace the scholarship of integration in SoTL, even though Ernest Boyer valued it as a continuous area of study. This article calls for a reconsideration of Boyer’s appreciation of integration as convergence or intertextuality. Intertextuality and its digital correlate, hypertextuality, operationalize online education. Yet, they are often ignored as models of convergence. This relational paradox signals a need for a discourse and framework that help us to conceptualize the inherently integrative nature of knowledge and online education. To address this deficit, this literature review introduces Peircean architectonics as the paradigm that reframes our understanding of convergence and illuminates its actualization in Terry Anderson’s prototype for online education. Architectonic logic enriches this model and provides us with a philosophy of convergence that revalues and advances the scholarship of integration.